KECEMASAN PASIEN YANG MENJALANI PEMINDAIAN CT-SCAN KEPALA: ANXIETY OF PATIENTS UNDERGOING HEAD CT-SCAN IMAGING - Pratama, Tisna Sendy; Septianawati, Paramita; Maulana, Andi Muh.; Fakih, Mohammad; Dwi Yuliani, Massita (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Head computed tomography (CT) scan is one of the diagnostic procedures that is often used to evaluate the condition of the brain and other head structures. This study aims to analyze the relationship between demographic factors, medical history, and patient perceptions and experiences with anxiety levels during radiological examinations. Using a cross-sectional analytical approach, the study involved 36 patients who were going to undergo a head CT scan. Data collection was carried out through a comprehensive questionnaire covering demographic and psychological aspects using the DASS-21. The results of the study revealed that patient anxiety was significantly related to a history of chronic disease, concerns about the narrow scanner space, distrust of examination technology, lack of information, and fear of radiation exposure. In contrast, factors such as gender, age, and history of trauma did not show significant correlations. In conclusion, radiological examinations often cause patient anxiety due to the characteristics of the narrow scanner and the use of radiation. The level of anxiety is influenced by various personal and medical factors, including medical history, previous experiences, and individual perceptions of the examination procedure. Therefore, educational interventions that increase understanding and relieve patient concerns can be effective in reducing anxiety levels during radiological examinations.